ANALISIS EFISIENSI TEKNIS USAHA TERNAK KAMBING PERANAKAN ETAWA (Studi Kasus di Kelompok Agribisnis As-Salam Kota Tasikmalaya) - Siti Maemunah; Dedi Sufyadi; Ida Hodiyah (Universitas Galuh Ciamis, 2017)
The purpose of this study was to determine: (1) The factors that affect the production of PE goats in Agribusiness Farmers Group As-Salam, and (2) The level of technical efficiency is achieved on PE goat raising in Agribusiness Farmers Group As-Salam.The research was conducted by using a case study on agribusiness farmer group As-Salam consisting of 26 people and all of them were taken as a sample or census conducted. Factors that affect the production of milk goats and technical efficiency levels achieved on PE goat raising in Agribusiness Farmers Group As-Salam analyzed using stochastic frontier production function where the parameter estimation is done using software Front41.The results showed: (1) The factors that affect the production of milk PE goats in Agribusiness Farmers Group As-Salam is the number of livestock ownership, labor, feed concentrates and drugs. While forage no significant effect on PE goat milk production, and (2) The level of technical efficiency is achieved on PE goat raising in Agribusiness Farmers Group As-Salam ranged from 39.78% to 99.04% with an average of 77.46%. Farmers who achieve technical efficiency above 70% as many as 17 people, while achieving technical efficiency below or equal to 70% as many as 9 peoples.